(3QSGdI CNQj aj GdeYGOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI GdMeO ddg Cgd cd MeO hHYO agPg QSGdI YedJgG HGSe HYV GdNdU ef GdCNhGf eTJYdI Ydi aNQ eG JDOj Edjg GdHQGgje ef MGd GdfaS GdfGWbI s
(3BNQgG (B:s
(3Ke MQeJ Ydi LejY ef jbQCg ef GdENhGf ZjQ ehVY hLYdJ Gddg NUeg Yfi hgh GdeSFhd s
(3Vef eLehY , JQJjHgG (B: 13s
(3hjXf CfgG QSGdI ai GdfaSs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs